New anti-friction self-lubricating composite based on EP975 nickel alloy powder with CaF2 solid lubricant – Thermal and dilatometric behavior - Adam Kurzawa; Mateusz Stachowicz; Maciej Roszak; Tetiana Roik; Oleg Gavrysh; Iulia Maistrenko; Krzysztof Jamroziak; Mirosław Bocian; Grzegorz Lesiuk (Alexandria Engineering Journal)
Dilatometric phenomena, mechanical and antifriction properties of a new high-temperature composite based on powder nickel alloy EP975 with additives (4.0˗8.0)% CaF2 solid lubricant have been investigated. New composite has been manufactured using hot isostatic pressing (HIP) technology with subsequent hardening heat treatment. Antifriction properties showed the advantages of the studied composite (improved friction coefficient and friction wear at elevated temperature). The authors analyzed the thermal, mechanical, wear structural and chemical phenomena of the new high-temperature antifriction composite developed to operate at high temperatures (800˗900 °C). Samples were tested with triple heating up to 1000 °C at different heating rates. SEM and EDS tests have shown that phase transformations and oxidation processes during high-temperature heating lead to the formation of new phases occurring from the boundaries between the CaF2 particles and the Ni matrix of the composite, which leads to local segregations and the formation of new phases cause changes in their crystallographic parameters under the influence of high temperatures and their integral effect leads to significant dilatometric phenomena at high temperatures. The data obtained opens up the possibility of clearly selecting the operating temperatures of a bearings made from new composite, taking into account dilatometric phenomena in specific temperature ranges.